The Impact of Vocational Education on the Economic Growth of Indonesian Human Resources - A. Nur Fitrianti (IECON, 2024)
This research aims to analyze the impact of vocational education on the availability of skilled labor and the economic growth of human resources (HR) in Indonesia. As industrial needs become increasingly complex and specific, vocational education is expected to provide appropriate skills for the workforce so as to increase productivity and competitiveness. In this research, vocational education is used as an independent variable, availability of skilled labor as a mediating variable, and economic growth of human resources as a dependent variable. The research uses the path analysis method to test the direct and indirect relationships between the variables involved. Data was collected from vocational school graduates and companies that employ skilled workers in various industrial sectors in Indonesia. The research results show that vocational education has a significant positive effect on the availability of skilled labor, and the availability of skilled labor has a significant positive effect on the economic growth of human resources. In addition, it was found that the availability of skilled labor mediates the effect of vocational education on human resource economic growth, with a significant mediation effect. These findings show the important role of vocational education in increasing the availability of skilled labor that is relevant to market needs. Therefore, it is recommended that there be increased synergy between vocational education institutions and the industrial sector to optimize the curriculum according to industrial skills needs. It is hoped that the results of this research can contribute to the development of vocational education policies and competitive human resource development strategies in Indonesia.